Aberrant insular cortex connectivity in abstinent alcohol‐dependent rats is reversed by dopamine D3 receptor blockade. (24th March 2019) - Scuppa, Giulia; Tambalo, Stefano; Pfarr, Simone; Sommer, Wolfgang H.; Bifone, Angelo
Abstract: A few studies have reported aberrant functional connectivity in alcoholic patients, but the specific neural circuits involved remain unknown. Moreover, it is unclear whether these alterations can be reversed upon treatment. Here, we used functional MRI to study resting state connectivity in rats following chronic intermittent exposure to ethanol. Further, we evaluated the effects of SB‐277011‐a, a selective dopamine D3 receptor antagonist, known to decrease ethanol consumption. Alcohol‐dependent and control rats ( N  = 13/14 per group), 3 weeks into abstinence, were administered SB‐277011‐a or vehicle before fMRI sessions. Resting state connectivity networks were extracted by independent component analysis. A dual‐regression analysis was performed using independent component maps as spatial regressors, and the effects of alcohol history and treatment on connectivity were assessed. A history of alcohol dependence caused widespread reduction of the internal coherence of components. Weaker correlation was also found between the insula cortex (IC) and cingulate cortices, key constituents of the salience network. Similarly, reduced connectivity was observed between a component comprising the anterior insular cortex, together with the caudate putamen (CPu‐AntIns), and the posterior part of the IC. On the other hand, postdependent rats showed strengthened connectivity between salience and reward networks. In particular, higher connectivity was observed between insula and nucleus accumbens, between the ventral tegmental area and the cingulate cortex and between the VTA and CPu‐AntIns. Interestingly, aberrant connectivity in postdependent rats was partially restored by acute administration of SB‐277011‐a, which, conversely, had no significant effects in naïve rats. Abstract : We used a rodent model of alcohol dependence to investigate the effect of chronic ethanol exposure on brain functional connectivity and test the hypothesis that alcohol‐induced alterations could be reversed by pharmacotherapy. Results showed widespread activation during early abstinence with a prominent involvement of the insular cortex (eg, salience network). Further, we demonstrate that aberrant connectivity in "abstinence network" can be restored by the administration of SB‐277011a, a D3 selective antagonist with efficacy in attenuating alcohol seeking in the rat, suggesting that fMRI‐derived brain connectivity networks could be a potential biomarker for medication development.